Pengoperasian Shotblasting Machine (Tochu) TG-7.5 FTJ Menggunakan Motor Induksi 3 Phasa pada Proses Repaint Tabung Gas LPG 3 Kg di PT. Gasbumi Sarana Karya - Aula Rizqiyana; Mohammad Fatkhurrokhman (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study discusses the operation of the Shotblasting Machine (TOCHU) TG-7.5 FTJ using a 3-phase induction motor in the repainting process of 3 kg LPG gas cylinders at PT. Natural Gas Facilities Karya. The purpose of this study is to know and analyze the operation of the Shotblasting Machine (TOCHU) TG-7.5 FTJ using a 3-phase induction motor in the 3 kg LPG gas cylinder repaint process at PT. Natural Gas Facilities Karya. This research was conducted by direct observation technique, interview and literature study. The results of this study indicate that shotblasting is one of the easiest methods to remove rust and dirt such as oil, paint, and so on. The operating system of the Shotblasting Machine (Tochu) TG-7.5 FTJ requires standard guidelines and procedures to avoid obstacles and errors that may be fatal. The induction motor is able to move the components of the shotblasting machine which can facilitate the repaint process consisting of the process of moving 3 kg LPG gas cylinders on the roller, the blasting process, the process of transferring the steel shot blast material to the bucket elevator, the process of collecting iron sand on the screw conveyor, the process of absorbing the remaining paint dust. on dust collectors. Keywords: Motor, Shotblasting Machine, Repaint